Media and Convergence Management - Diehl, Sandra; Karmasin, Matthias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Convergence has gained an enormous amount of attention in media studies within the last several years. It is used to describe the merging of formerly distinct functions, markets and fields of application, which has changed the way companies operate and consumers perceive and process media content. These transformations have not only led business practices to change and required companies to adapt to new conditions, they also continue to have a lasting impact on research in this area. This book$1 (Bs main purpose is to shed some light on crucial phenomena of media and convergence management, while also addressing more specific issues brought about by innovations related to media, technologies, industries, business models, consumer behavior and content management. This book gathers insights from renowned academic researchers and pursues a highly interdisciplinary approach. It will serve as a valuable reference guide for students, practitioners and researchers interested in media convergence processes.s
Introduction -- Part I: Convergence and Strategic Management -- Part II: Convergence and Advertising and Marketing -- Part III: Convergence and Consumer Behavior -- Part IV: Convergence and Technology -- Part V: Convergence and Journalism -- Part VI: Future Outlook.
Keywords: Economics; Mass media; Economics/Management Science; Media Management; Media Research; Communication Studies